2012
DOI: 10.5147/jpgs.2012.0053
|View full text |Cite
|
Sign up to set email alerts
|

The ‘PI 438489B’ by ‘Hamilton’ SNP-Based Genetic Linkage Map of Soybean [Glycine max (L.) Merr.] Identified Quantitative Trait Loci that Underlie Seedling SDS Resistance

Abstract: Soybeans [Glycine max (L.) Merr.] are susceptible to many diseases including fungal diseases such as soybean sudden death syndrome (SDS). Several studies reported SDS resistance quantitative trait loci (QTL) on the soybean genome using different recombinant inbred line (RIL) populations and low density genetic linkage maps. High density exclusively single nucleotide polymorphisms-based (SNP-based) maps were not yet reported in soybean. The objectives of this study were (1) to construct a high density SNP-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 48 publications
(82 reference statements)
3
21
1
1
Order By: Relevance
“…The identification of genes within the QTL regions was performed as described earlier (Barakat, Staton, Cheng, Park, Yassin, Ficklin, Yeh, Hebard, & Sederoff, 2012;Kassem et al, 2012). Briefly, each QTL was bounded by two single nucleotide polymorphism markers (SNPs).…”
Section: Analysis Of Qtl Regions For Candidate Genesmentioning
confidence: 99%
“…The identification of genes within the QTL regions was performed as described earlier (Barakat, Staton, Cheng, Park, Yassin, Ficklin, Yeh, Hebard, & Sederoff, 2012;Kassem et al, 2012). Briefly, each QTL was bounded by two single nucleotide polymorphism markers (SNPs).…”
Section: Analysis Of Qtl Regions For Candidate Genesmentioning
confidence: 99%
“…The 'PI 438489B' By 'Hamilton' RIL population (PIxH, n=50) used in this study was developed at the University of Missouri Agronomy Research Center (Yue, Arelli, & Sleper, 2001) and was extensively studied to map QTL for SDS resistance (Kassem et al, 2012), SCN resistance (Yue et al, 2001). …”
Section: Plant Materialsmentioning
confidence: 99%
“…A particularly important advantage of the Illumina-based SNP allele detection over the SSR marker allele detection is the elimination of the tedious gel-based marker allele visualization required for the latter. The SNP-based genetic linkage map (Kassem et al, 2012) was used for genetic analysis of yield components of a soybean RIL population in this study.…”
Section: Introductionmentioning
confidence: 99%
“…On chromosome 1 (LG D1a) 'qOIL001' was identified to be associated with the oil trait by the marker interval ss107915391-ss107917465. On the same chromosome, QTL for soybean sudden death syndrome (SDS) (Kassem et al, 2012) and soybean cyst nematode (SCN) resistance were previously identified using the same soybean population. QTL for several other agronomic traits such as Japanese root-knot nematode resistance, protein concentration, oil content, and leaf length, were also identified in the same chromosome 1 (LG D1a;SoyBase, 2012 (Orf et al, 1999;Mansur, Lark, Kross, & Oliveira, 1993;Mansur et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…All of these interfered in QTLs to improve protein and oil content of soybean by marker-assisted selection (MAS). On the other hand, several studies reported SNP markers associated with QTL for several traits in soybean (Vuong, Wu, Pathan, Valliodan, & Nguyen, 2007), but there are only two studies reported an exclusively SNP-based genetic map (Kassem, 2012;Hyten et al, 2010a). The genetic relationship between moisture, protein, oil and other traits could be explored by comparing QTL mapping results when available and fine mapping of each trait would provide accurate genetic information.…”
Section: Discussionmentioning
confidence: 99%